IMPLEMENTASI TEORI PEMBELAJARAN KONSTRUKTIVISME DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN FIKIH DI MTS PLUS ATH THOHIRIYAH KEDUNGPRING - farikh, Achmad Farikh Padliloh; Siti Suwaibatul Aslamiyah (Universitas Islam Lamongan, 2025)
This study aims to describe the implementation of constructivist learning theory in improving students' understanding of fiqh subjects at MTs Plus Ath Thohiriyah Kedungpring. This research uses a qualitative descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study show that the application of constructivist theory through the planning, implementation, and evaluation stages succeeded in creating a dynamic and participatory learning atmosphere. The teacher provides stimuli in the form of concept maps and group assignments, while students actively build their own knowledge through discussions and direct experiences. This implementation has been proven to increase students' understanding of fiqh material, especially the chapter on halal and haram food and beverages.